Tremor after head injury and its treatment by stereotaxic surgery. - Andrew, J (1982)
Tremor, both postural and kinetic may be a late complication for victims of severe closed head injury, especially in the young, and may add to their disability. The nature of the tremor is described in eight patients. In each a stereotaxic thalamotomy was performed, dramatically relieving or reducing the severity of tremor in each instance, and resulting in improved function of the affected limb and increased independence. The site of the responsible lesion, which is thought to lie in the mid brain, is discussed together with the indications and contraindications for surgical management.